- BUYING AND SELLING K-POP PHOTOCARD: A REVIEW OF FIQH MUAMALAH AND CHALLENGES IN INTERNATIONAL TRANSACTIONS : - - Insani, Hasna Mutia; Faturrahman SW, Oman (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
The K-Pop phenomenon that has entered Indonesia has given birth to various new consumption cultures, one of which is photocard buying and selling. As a form of support for their idols, fans usually collect merchandise or photocards of their idols. The purpose of this study is to analyze how photocard buying and selling transactions between countries are viewed from the perspective of fiqh muamalah and identify the challenges that arise in international transactions. This research uses qualitative analysis as a research method with an empirical approach. The type of data used in the research is data obtained directly from the field. Data sources consist of primary data and secondary data. The data collection techniques applied are observation, interview and literature study. The results of the study show that the sale and purchase of photocard transactions between countries is permitted as long as it fulfills the legal conditions of sale and purchase. Keywords: Sale and Purchase, K-Pop Photocard, Fiqh Muamalah